Cardiovascular Alterations and Management of Patients With White Coat Hypertension: A Meta-Analysis - Xiang, Huaqiang; Xue, Yangjing; Wang, Jinsheng; Weng, Yingbei; Rong, Fangning; Peng, Yangpei; Ji, Kangting (Frontiers in Pharmacology, 2020)
A large and growing body of literature has focused on the association between “white coat hypertension” (WCH) and the underlying target organ damage. The evidence suggests that WCH is may not an entirely benign phenomenon. However, whether patients with WCH should receive antihypertensive drugs is unresolved. Therefore, we performed a meta-analysis to fully determine the ability of WCH to alter cardiovascular structure and to determine whether patients with WCH could benefit from drug intervention. Medline, EMBASE, and the Cochrane Library were searched from inception through 21 Oct 2019. A total of 25 studies (8100 individuals) were included. In participants with WCH, values of aortic pulse wave velocity, augmentation index, intima–media thickness, interventricular septum thickness, left ventricular posterior wall thickness, and left ventricular mass index were lower than those with sustained hypertension, but greater than those in the normotensive group. Of note, drug therapy did not reduce the risk of cardiovascular events in patients with WCH. WCH is accompanied by alterations of cardiovascular structure; however, the benefits from antihypertensive therapy are limited.